Penerapan nilai-nilai pemasaran Islami dalam menarik konsumen di Xifrahijab.id - Vika Sayyidatul Mukarromah; Aun Falestien Faletehan (JURNAL ADMINISTRASI KANTOR, 2024)
This study aims to analyze the application of Islamic values in marketing strategies used to attract consumer interest at the Xifrahijab.id online shop. Xifrahijab.id is a business focused on selling hijabs and Muslim women's clothing, emphasizing Islamic principles such as product halalness, honesty, fairness, and trustworthiness in every business process. This research uses a qualitative approach by conducting in-depth interviews with Xifrahijab.id customers and the owner. The findings show that the application of Islamic values in marketing such as providing honest product information, setting fair prices, and maintaining commitments to customers has increased consumer trust and loyalty. Additionally, the marketing strategy through social media, combined with special promotions during Ramadan, has proven effective in attracting consumer interest. Thus, the application of Islamic values not only serves as an ethical business guideline but also significantly contributes to enhancing competitiveness and commercial success. Keywords: Marketing strategy, Islamic values, Consumer purchasing interest, Online shop.